(untitled) (Journal of Global Accounting, 2022)
The study ascertain whether there is a significant difference between the pre and post COVID 19 pandemic on earning per share of industrial goods manufacturing companies in Nigeria. a sample of sixteen industrial goods companies was used for the study. Ex post Facto research design was employed for the study and data were extracted from annual accounts of the sampled companies in Nigeria from 2018 to 2021. Data extracted and analyzed and hypothesis was tested with regression analysis via E-View 9.0. The results shows that earnings per share have a positive effect on market price of industrial goods during the both periods, but pre COVID 19 pandemic was not significant while post COVID 19 was significant. The study therefore concluded that there is a significant difference between earnings per share and market price during pre and post COVID 19 pandemic in Nigeria. On that note, the study advised investors to keep in mind that earnings are a crucial factor in the development of share prices. As a result, earnings per share should be prioritized in the investor decision-making process.